2008
DOI: 10.1117/1.2993323
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantification of colonic crypt morphology using integrated microscopy and optical coherence tomography

Abstract: Colonic crypt morphological patterns have shown a close correlation with histopathological diagnosis. Imaging technologies such as high-magnification chromoendoscopy and endoscopic optical coherence tomography (OCT) are capable of visualizing crypt morphology in vivo. We have imaged colonic tissue in vitro to simulate high-magnification chromoendoscopy and endoscopic OCT and demonstrate quantification of morphological features of colonic crypts using automated image analysis. 2-D microscopic images with methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…OCT has strong translational potential for endoscopic imaging for identification of colonic pathologies [26-28] For FMI, besides the cathepsin-based contrast agents [23], Roney et al recently demonstrated that the legume lectin Ulex europaeus agglutinin I (UEA-1) binds the surfaces of adenomatous polyps in specimens of colorectal cancer from the APC Min mouse model. The carbohydrate α-L-fucose, which is over-expressed on the surfaces of polyps, facilitates the bond with UEA-1.…”
Section: Methodsmentioning
confidence: 99%
“…OCT has strong translational potential for endoscopic imaging for identification of colonic pathologies [26-28] For FMI, besides the cathepsin-based contrast agents [23], Roney et al recently demonstrated that the legume lectin Ulex europaeus agglutinin I (UEA-1) binds the surfaces of adenomatous polyps in specimens of colorectal cancer from the APC Min mouse model. The carbohydrate α-L-fucose, which is over-expressed on the surfaces of polyps, facilitates the bond with UEA-1.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 These algorithms were developed for OCT images of other organs to investigate the diagnostic power. 20,21 CADx algorithms will be more important when large numbers of images need to be interpreted and as OCT imaging speed increases. Zuluaga et al 13 reported a higher average epithelial intensity in abnormal tissue than in normal tissue in premenopausal women.…”
Section: Background and Introductionmentioning
confidence: 99%
“…6 and 10 and also in previous studies [15,44,45], crypt morphology patterns were correlated with colon pathologies. OCM promises to facilitate the detection of dysplasia or differentiation between hyperplasic and adenomatous polyps in surveillance colonoscopy.…”
Section: Discussionmentioning
confidence: 78%